2022
DOI: 10.1039/d1ta08362g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the polymer electrolyte–Li metal interface on high-voltage solid-state batteries with Li-based additives inspired by the surface chemistry of Li7La3Zr2O12

Abstract: High-voltage Li metal solid-state batteries are in the spotlight of high energy and power density devices for the next generation of batteries. However, the lack of robust solid-electrolyte interfaces (SEI)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…This effect has been observed with several types of fillers, namely "passive" fillers such as SiO 2 , [114] ZrO 2 , [115] and Al 2 O 3 , [116] lithium-conductive fillers, [81] such as Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP), [41,117] garnets (e.g. Li 7 La 3 Zr 2 O 12 -LLZO and Li 7-x La 3 Zr 2-x Ta x O 12 -LLZTO), [118][119][120][121][122][123][124][125][126] argyrodites (Li 6 PS 5 Cl), [127] perovskites (e.g. Li 3/8 Sr 7/16 Ta 3/4 Zr 1/4 O 3 -LSTZ), [128] and cationic metal-organic frameworks (such as D-UiO-66-NH 2 ).…”
Section: Composite Polymer Electrolytesmentioning
confidence: 99%
“…This effect has been observed with several types of fillers, namely "passive" fillers such as SiO 2 , [114] ZrO 2 , [115] and Al 2 O 3 , [116] lithium-conductive fillers, [81] such as Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP), [41,117] garnets (e.g. Li 7 La 3 Zr 2 O 12 -LLZO and Li 7-x La 3 Zr 2-x Ta x O 12 -LLZTO), [118][119][120][121][122][123][124][125][126] argyrodites (Li 6 PS 5 Cl), [127] perovskites (e.g. Li 3/8 Sr 7/16 Ta 3/4 Zr 1/4 O 3 -LSTZ), [128] and cationic metal-organic frameworks (such as D-UiO-66-NH 2 ).…”
Section: Composite Polymer Electrolytesmentioning
confidence: 99%
“…There are likely two main causes of the poor performance of all-PEO-based cells (Figure a,b): first, the parasitic reactions from the TFSI – counterion (driven by the low T Li + value of LiTFSI) seem to limit the charge cutoff voltage to 3.9 V (Figure a), and second, the degradation of PEO above this potential leading to an increase in the Ohmic drop (Figure b). The reaction between TFSI – anions and Li metal has been widely discussed in the literature, comprising a wide range of mechanisms. Golozar et al showed the accumulation of TFSI – in the vicinity of damaged Li-metal regions . They suggested a gradual decomposition of LiTFSI by multiple reduction steps, forming subunits such as Li x CNF 3 and Li y SO x through the reduction of the anion.…”
mentioning
confidence: 99%
“…However, Ranque et al showed that a LiOH shell surrounding LLZO facilitated Li + -ion transfer between PEO and LLZO in a CSE, demonstrating that LiOH might not deter ion transport . Importantly, Orue et al similarly found that LiOH enhances the cyclability of CSEs by promoting a LiF-rich interface and a wide voltage window …”
Section: Introductionmentioning
confidence: 99%
“…Inorganic-derived species are considered beneficial to the SEI in liquid-based batteries because they transport Li + but insulate the electrolyte from electrons . Similarly, SEI and interfacial chemistry can be important in SSBs and can be adjusted by the strategic use of additives that affect the SEI such as LiF, LiNO 3 , Al 2 O 3 , and LiOH. ,,, Such additives can promote the growth of a more stable, inorganic-rich SEI. The SEI at the Li 0 anode in SSBs has been shown to contain lithium hydroxide (LiOH), lithium carbonate (Li 2 CO 3 ), and some lithium fluoride (LiF), but how the choice of additives controls the composition of the SEI and how the inorganic compounds stabilize the interfaces is not fully understood .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation